HUBUNGAN KOORDINASI MATA DAN KAKI DAN POWER OTOT TUNGKAI DENGAN HASIL SHOOTING KE GAWANG DALAM PERMAINAN SEPAKBOLA DI SSB SAP SUNGAI APIT KECAMATAN SUNGAI APIT KABUPATEN SIAK - Azizurrohman, Oktafinandi; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is conducted to see any possible relation between eye-leg coordination and power of leg muscles toward the outcome of goal shooting in a soccer game in SSB SAP Sungai Apit in Sungai Apit Sub district, Siak Regency. The sample used in this research is a team of 16 soccer players of SSB SAP Sungai Apit in Sungai Apit Sub district, Siak Regency. The sampling method of this research is total sampling using all 16 soccer players of SSB SAP Sungai Apit in Sungai Apit Sub district, Siak Regency. The result of the first correlation analysis of X1 and Y shows a strong where is on significance level of ɑ (0.05) = 0,880) > (0.514), which means hypothesis is accepted. Meanwhile, the calculation of the second analysis of X2 and Y also shows a strong where is on significance level of ɑ (0.05) = 0,791) > (0.514) which means hypothesis is accepted too. Lastly, on the third analysis to see the relation between X1 and X2 toward Y where is on significance level of ɑ (0.05) = 0,880) > (0.514), it can be concluded that X1 and X2 are strongly related to Y. Keywords : Eye-leg coordination, power of leg muscles, the outcome of goal shooting